Mold release film and method for manufacturing semiconductor package
By designing a three-layer release film, the problems of surface damage and electrostatic discharge of semiconductor packages are solved, good demoulding properties and laser marking recognition are achieved, and the appearance quality is improved.
Patent Information
- Application Number
- CN202480010360.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-03
- Filing Date
- 2024-01-31
- Publication Date
- 2025-09-12
AI Technical Summary
Existing release films are prone to damage and stains on the surface of semiconductor packages, resulting in a decrease in appearance quality. In addition, during the peeling process, they are prone to electrostatic discharge, which can damage components. At the same time, the contrast between the marked and non-marked areas is increased, leading to misreading of identification information.
The release film adopts a three-layer structure, including a release layer, an antistatic layer and a substrate. The thickness of the release layer is greater than 0.1μm, the surface concave-convex angle distribution of the antistatic layer side is within the range of 10-35°, the existence fraction is above 0.12, the surface roughness of the substrate is above 0.9μm, and fluororesin is used as the main material to ensure good antistatic and release properties.
It improves the visibility of laser markings on the surface of semiconductor packages, reduces the visibility of resin flow marks and damage, improves the appearance quality, and effectively prevents electrostatic discharge damage.
Smart Images

Figure BDA0005527229780000411 
Figure BDA0005527229780000421 
Figure BDA0005527229780000431
Abstract
Description
Technical Field
[0001] The present invention relates to a release film and a method for manufacturing a semiconductor package. Background Art
[0002] Semiconductor packages have a resin sealing portion that protects semiconductor elements. Curable resins such as thermosetting epoxy resins are widely used to form the resin sealing portion. As methods for sealing semiconductor components, compression molding and transfer molding are known. These methods involve placing a substrate with a semiconductor component mounted within a mold cavity, which is then filled with a curable resin to form a resin seal. In these sealing methods, a release film is typically placed on the mold cavity surface to prevent the resin seal from solidifying with the mold. In this case, the surface shape of the release film is transferred to the surface of the resin seal.
[0003] Furthermore, sealed semiconductor packages are laser-marked with identification information such as the manufacturer's name, product name, and batch number for traceability and assurance. Poor visibility of the markings can lead to problems such as product identification between the manufacturer and the user.
[0004] In such circumstances, for example, Patent Document 1 proposes a release film having a surface smoothness (Ra) of 0.1 to 0.5 μm and an average spacing of irregularities (RSm) of 90 to 125 μm. Use of this release film increases the contrast between the non-marked area and the marked area, improving the visibility of the marked area. Prior art literature Patent Literature
[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 2014-179593 Summary of the Invention Technical problem to be solved by the invention
[0006] However, scratches, stains, and other defects on the surface of semiconductor packages can sometimes cause problems with their appearance. To make these minor scratches less noticeable, the surface of semiconductor packages is often given a slightly roughened, matte finish, rather than a mirror finish. Increasing the contrast between the non-marking area and the marking area, as in Patent Document 1, makes scratches and other defects in the non-marking area more noticeable, tending to reduce the appearance. Furthermore, these scratches can sometimes lead to misreading of identification information.
[0007] Furthermore, in recent years, the line widths of semiconductor devices have become increasingly narrow, making ESD (electrostatic discharge), which previously did not pose a problem, more likely to cause insulation breakdown in semiconductor devices. When using a release film to seal semiconductor devices in the manufacture of semiconductor packages, the release film must be peeled off from the resin seal after the curable resin is cured to form the resin seal. This peeling process also requires suppressing ESD.
[0008] The present disclosure provides a release film having excellent antistatic properties and releasability from a semiconductor package and capable of forming a semiconductor package surface with excellent laser marking visibility, and a method for manufacturing a semiconductor package using the release film. Technical solutions used to solve technical problems
[0009] In order to overcome the above technical problems, the following specific measures are adopted: <1> A release film, It is a release film comprising a release layer, an antistatic layer and a substrate in this order, wherein: The average thickness of the release layer is greater than 0.1 μm, When the surface irregularities on the release layer side of the release film are measured using a laser microscope and the surface angle distribution of the angle (θ) formed by the normal vector of the irregularities and the normal to the main surface of the release film is calculated, the existence fraction (Φ) in the range of 10 to 35° is greater than 0.12. <2> The release film according to <1>, wherein an arithmetic mean height Sa of at least one surface of the substrate is 0.9 μm or more. <3> The release film according to <2>, wherein an arithmetic mean height Sa of the surface of the substrate on the antistatic layer side is 1.2 μm or more. <4> The release film according to any one of <1> to <3>, wherein the content of particles in the release layer is 25% by volume or less. <5> The release film according to any one of <1> to <4>, wherein the substrate comprises a fluororesin. <6> The release film according to <5>, wherein the fluororesin comprises an ethylene-tetrafluoroethylene copolymer. <7> The release film according to any one of <1> to <6>, wherein the surface resistivity of the release layer side surface is 1×10 7 ~1×10 11 Ω / □. <8> The release film according to any one of <1> to <7>, which is arranged between a curable resin and a surface of a mold in the production of a semiconductor package. <9> The release film according to <8>, wherein a surface of the release film on the release layer side is in contact with the curable resin. <10> A method for manufacturing a semiconductor package, The present invention relates to a method for manufacturing a semiconductor package having a semiconductor element and a resin sealing portion formed of a curable resin for sealing the semiconductor element, wherein: The substrate having the semiconductor element is arranged in the cavity of the mold, On the cavity surface of the mold where the substrate is not disposed, a release film according to any one of <1> to <9> comprising a release layer, an antistatic layer, and a base material is disposed so that the surface on the release layer side faces the space within the cavity. The cavity is filled with the curable resin, and the curable resin is cured in a state where the curable resin is in contact with the release film, thereby forming a resin sealing portion that seals the semiconductor element. Effects of the Invention
[0010] According to the present disclosure, a release film having excellent antistatic properties and releasability from a semiconductor package and capable of forming a semiconductor package surface with excellent laser marking visibility, and a method for manufacturing a semiconductor package using the release film can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 The figure shows the surface angle distribution and the existence fraction (Φ) in the range of 10 to 35 degrees. Figure 2 This is an explanatory diagram showing the angle (θ) formed between the normal vector of the concavities and convexities on the surface of the release film and the normal to the main surface of the release film. Figure 3 It is a cross-sectional view schematically illustrating a compression molding method as an example of a method for manufacturing a semiconductor package according to the present disclosure. Figure 4 It is a cross-sectional view schematically illustrating a compression molding method as an example of a method for manufacturing a semiconductor package according to the present disclosure. Figure 5 It is a cross-sectional view schematically illustrating a compression molding method as an example of a method for manufacturing a semiconductor package according to the present disclosure. Figure 6 1 is a cross-sectional view schematically illustrating a transfer molding method as an example of a method for manufacturing a semiconductor package according to the present disclosure. Figure 7 1 is a cross-sectional view schematically illustrating a transfer molding method as an example of a method for manufacturing a semiconductor package according to the present disclosure. Figure 81 is a cross-sectional view schematically illustrating a transfer molding method as an example of a method for manufacturing a semiconductor package according to the present disclosure. Figure 9 1 is a cross-sectional view schematically illustrating a transfer molding method as an example of a method for manufacturing a semiconductor package according to the present disclosure. Figure 10 1 is a cross-sectional view schematically illustrating a transfer molding method as an example of a method for manufacturing a semiconductor package according to the present disclosure. Figure 11 1 is a cross-sectional view schematically illustrating a transfer molding method as an example of a method for manufacturing a semiconductor package according to the present disclosure. DETAILED DESCRIPTION
[0012] The following describes the embodiments of the present disclosure in detail. However, the present disclosure is not limited to the following embodiments. In the following embodiments, the constituent elements (including element steps, etc.) are not required unless otherwise specified. The numerical values and their ranges are also not limiting to the present disclosure. In the present disclosure, the term "process" includes not only processes that are independent of other processes, but also processes that can achieve the purpose of the process even if the process cannot be clearly distinguished from other processes. In the present disclosure, a numerical range represented by “to” includes the numerical values described before and after “to” as a minimum value and a maximum value, respectively. In the numerical ranges described in this disclosure, the upper limit or lower limit of one numerical range may be replaced by the upper limit or lower limit of another numerical range described in the disclosure. In addition, in the numerical ranges described in this disclosure, the upper limit or lower limit of the numerical range may be replaced by the value shown in the Examples. In the present disclosure, each component may contain multiple corresponding substances. When multiple substances corresponding to each component are present in the composition, the content rate or amount of each component refers to the total content rate or total amount of the multiple substances present in the composition, unless otherwise specified. In the present disclosure, particles corresponding to each component may include multiple types of particles. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component refers to the value of the mixture of the multiple types of particles present in the composition, unless otherwise specified. In the present disclosure, the term "layer" includes not only a case where the layer is formed in the entire region when the region where the layer exists is observed, but also a case where the layer is formed in only a part of the region. While the present disclosure is described with reference to the accompanying drawings, the present disclosure is not limited to the accompanying drawings. The sizes of the components in the accompanying drawings are schematic, and the relative sizes of the components are not limited thereto.
[0013] "(Meth)acrylate" is a general term for acrylate and methacrylate. An "acrylic polymer" refers to a polymer having units derived from (meth)acrylate. The units derived from (meth)acrylate contained in the acrylic polymer may be one type or two or more types. The acrylic polymer may further have units derived from other monomers besides the units derived from (meth)acrylate. In the present disclosure, units based on monomers are sometimes represented by the monomer name plus the unit, such as ethylene units.
[0014] In this disclosure, “laser mark visibility” refers to visibility under Automatic Visualization Inspection (AVI). In AVI, brightness is measured by a detector located at 90° to light incident at a specific angle relative to the horizontal plane of the semiconductor package surface.
[0015] In the present disclosure, the arithmetic mean height Sa is measured in accordance with ISO-25178-2: 2012. The measurement is performed using a laser microscope at an ambient temperature of 23 to 25°C.
[0016] Release film The release film disclosed herein is a release film comprising a release layer, an antistatic layer, and a substrate in this order. The release layer has an average thickness of greater than 0.1 μm. When the surface irregularities of the release layer side of the release film are measured using a laser microscope and the surface angle distribution of the angle (θ) formed between the normal vector of the irregularities and the normal to the main surface of the release film is calculated, the existence fraction (Φ) in the range of 10 to 35° is greater than 0.12.
[0017] The above configuration enables formation of a semiconductor package surface having excellent antistatic properties, excellent releasability from the semiconductor package, and excellent laser marking visibility. The reason for this is presumably as follows, but the present invention is not limited to the following presumption.
[0018] When an antistatic layer is provided on a release film for the purpose of suppressing ESD, a further release layer is often provided on the antistatic layer to improve the releasability from the sealing resin. If the release layer is too thin, the releasability from the resin sealing portion is likely to be insufficient. The release film of the present disclosure comprises a release layer, an antistatic layer, and a substrate in order from the side in contact with the curable resin, and thus has excellent antistatic properties. The release layer has an average thickness of more than 0.1 μm, thereby ensuring releasability.
[0019] Furthermore, in the release film of the present disclosure, when the surface irregularities on the release layer side (the surface of the release film on the side where the release layer is present relative to the substrate, hereinafter also referred to as the "first surface") are measured using a laser microscope and the surface angle distribution of the angle (θ) formed between the normal vector of the irregularities and the normal to the main surface of the release film is determined, the presence fraction (Φ) in the range of 10 to 35° is greater than 0.12. In addition, when an antistatic layer and a release layer are formed by coating a substrate having a concave-convex surface to prepare a release film, the properties of the angles of the surface concave and convex parts will change before and after coating. Since the coating liquid easily accumulates in the concave parts of the substrate, if each layer is formed on the substrate by coating, there is a tendency for the surface angle at the concave part to be gentler than that at the convex part as a change before and after coating. The recognizability is affected by the overall surface shape of the concave-convex surface, so in the release film of the present invention manufactured by this manufacturing method, the surface roughness of the substrate and the average thickness of the antistatic layer and the release layer are controlled to optimize the overall surface shape of the concave and convex parts. As a result, it is preferred that the existence fraction (Φ) in the range of 10 to 35° is above 0.12 to improve the laser marking recognizability.
[0020] First, the method of finding the existence fraction (Φ) is described. The surface shape of the release film was measured using a laser microscope in accordance with ISO-25178-2:2012 at an ambient temperature of 23-25°C, using 0.25 μm increments for both the X and Y coordinates. The obtained X, Y, and Z coordinate (height) data were used to determine the normal vector of the concave and convex surfaces at each point using the surfnorm function in MATLAB (registered trademark) R2022b. The angle (θ) formed between the normal vector of the concave and convex surface and the normal to the main surface of the release film was calculated at each point and histogrammed at 0.1° increments to determine the surface angle distribution. Figure 1 Shown is an example of the surface angle distribution. Figure 1 In the surface angle distribution diagram, the area ratio of angles (θ) in the range of 10 to 35° relative to the total area of all angles 0 to 90° is calculated, which is the existence fraction (Φ) in the range of 10 to 35°.
[0021] Here, use Figure 2 The angle (θ) formed by the normal vector of the concavo-convex surface on the first surface of the release film and the normal line of the main surface of the release film is described. Figure 2 As shown, in the release film 30, the angle θ is formed between the normal line N of the main surface S having the concavo-convex 32 and the normal vector L of the concavo-convex 32. The main surface S is a surface extending perpendicular to the thickness direction of the release film, and the normal line N of the main surface S can also be referred to as the thickness direction of the release film.
[0022] Therefore, the existence fraction (Φ) within the range of 10 to 35° refers to the ratio of angles of 10 to 35° among the angles formed by the normal vectors of the surface irregularities of the release film relative to the normal to the main surface of the release film. For example, when observing light from the top of the release film, i.e., in the direction normal to the main surface of the release film, light incident at an angle of 20° to the normal to the main surface of the release film is reflected from the surface with an angle (θ) of 10°. Furthermore, light incident at an angle of 70° to the normal to the main surface of the release film is reflected from the surface with an angle (θ) of 35°. Therefore, when the angle (θ) is 10 to 35°, light incident at an angle of 20 to 70° relative to the normal to the main surface of the release film is reflected along the normal to the main surface of the release film, and this light is easily visible from above the release film. The surface irregularities of the release film are transferred to the surface of the semiconductor package. The surface of the semiconductor package forms a reversed version of the surface irregularities of the release film. The angle formed between the normal vectors of the irregularities on the semiconductor package surface and the normal to the horizontal plane of the semiconductor package surface is the same as the angle (θ) at the corresponding portion of the release film surface. Therefore, the optical visibility of the semiconductor package surface is believed to be the same as that of the release film surface. Therefore, the inventors discovered through experiments that if the existence fraction (Φ) of the release film in the angle (θ) range of 10 to 35° is greater than 0.12, the print recognition of the laser mark on the surface of the semiconductor package is excellent when using AVI inspection with a detector located at a position 90° relative to the horizontal plane of the semiconductor package surface.
[0023] The existence fraction (Φ) in the range of 10 to 35° is greater than 0.12. From the perspective of maintaining the laser marking recognizability while making the resin flow marks (flow marks) on the surface of the semiconductor package or the damage on the package surface inconspicuous, that is, improving the appearance quality, it is preferably greater than 0.14, and more preferably greater than 0.15. Furthermore, from the viewpoint of further improving the laser marking visibility, the existence fraction (Φ) in the range of 10 to 35° is preferably 0.66 or less, more preferably 0.65 or less, and even more preferably 0.64 or less.
[0024] The release film disclosed herein can be used, for example, between a curable resin and a mold surface during the manufacture of semiconductor packages. Preferably, the release film is positioned so that the release layer side (first surface) of the release film contacts the curable resin. During the manufacture of semiconductor packages, a semiconductor element is placed within a mold and sealed with a curable resin to form a resin seal.
[0025] (Base material) The material (composition included) constituting the substrate is not particularly limited, and known materials such as resins for release films can be applied. As the resin used for the substrate, from the perspective of excellent releasability of the release film from the mold after sealing, it is preferably a resin with releasability. A resin with releasability means that only the layer formed by the resin has releasability. As the resin with demoulding properties, fluororesin, polymethylpentene, syndiotactic polystyrene, polycycloolefin, silicone rubber, polyester elastomer, polyethylene terephthalate, polybutylene terephthalate, non-stretched nylon, etc. can be cited. Considering the demoulding properties of the mold, the heat resistance at the temperature of the mold during sealing (e.g., 180° C.), the flow of the curable resin and the strength capable of withstanding the applied pressure, the elongation at high temperature, etc., fluororesin, polymethylpentene, syndiotactic polystyrene, polycycloolefin, etc. are preferred. From the perspective of excellent demoulding properties, fluororesin is particularly preferred. That is, the substrate preferably contains fluororesin. These resins can be used alone or in combination of two or more.
[0026] The content of the fluororesin in the entire resin contained in the substrate is preferably 80 mass % or more, more preferably 90 mass % or more, further preferably 95 mass % or more, particularly preferably 99 mass % or more, and may be 100 mass %. As fluororesins, fluoroolefin polymers are preferred from the perspective of excellent mold release and heat resistance. Fluoroolefin polymers are polymers having units based on fluoroolefins. Fluoroolefin polymers may also have units other than units based on fluoroolefins.
[0027] Examples of the fluoroolefin include tetrafluoroethylene (hereinafter also referred to as "TFE"), vinyl fluoride, vinylidene fluoride, trifluoroethylene, hexafluoropropylene, and chlorotrifluoroethylene. The fluoroolefin may be used alone or in combination of two or more. Examples of the fluoroolefin polymer include ethylene-tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer (PFA), and tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer (THV). The fluoroolefin polymer may be used alone or in combination of two or more. As a fluoroolefin polymer, ETFE is particularly preferred due to its high elongation at high temperatures. ETFE is a copolymer having TFE units and ethylene units (hereinafter also referred to as "E units"). That is, ETFE is preferred as the fluororesin contained in the substrate.
[0028] In addition to the TFE unit and the E unit, ETFE can also have a unit based on a third monomer. The third monomer can be used alone or in combination of two or more. As the third monomer, monomers having fluorine atoms and monomers not having fluorine atoms can be enumerated.
[0029] Examples of the monomer having a fluorine atom include the following monomers (a1) to (a5). Monomer (a1): Fluoroolefins having 2 or 3 carbon atoms. Monomer (a2): X(CF2) n Fluorinated alkylethylenes represented by CY=CH2 (wherein X and Y are each independently a hydrogen atom or a fluorine atom, and n is an integer of 2 to 8). Monomer (a3): Fluorinated vinyl ethers. Monomer (a4): Fluorinated vinyl ethers containing functional groups. Monomer (a5): a fluorine-containing monomer having an aliphatic ring structure.
[0030] Examples of the monomer (a1) include fluoroethylenes (trifluoroethylene, vinylidene fluoride, vinyl fluoride, chlorotrifluoroethylene, etc.), fluoropropylenes (hexafluoropropylene (hereinafter also referred to as "HFP"), 2-hydropentafluoropropylene, etc.), and the like.
[0031] As the monomer (a2), monomers in which n is 2 to 6 are preferred, and monomers in which n is 2 to 4 are particularly preferred. In addition, monomers in which X is a fluorine atom and Y is a hydrogen atom, that is, (perfluoroalkyl)ethylenes are particularly preferred. Specific examples of the monomer (a2) include the following compounds. CF3CF2CH=CH2、 CF3CF2CF2CF2CH=CH2((perfluorobutyl)ethylene, hereinafter also referred to as "PFBE"), CF3CF2CF2CF2CF=CH2、 CF2HCF2CF2CF=CH2、 CF2HCF2CF2CF2CF=CH2, etc.
[0032] Specific examples of the monomer (a3) include the following compounds: Among the following compounds, the diene monomer is a cyclopolymerizable monomer. CF2=CFOCF3, CF2=CFOCF2CF3、 CF2=CFO(CF2)2CF3 (perfluoro(propyl vinyl ether), hereinafter also referred to as "PPVE"), CF2=CFOCF2CF(CF3)O(CF2)2CF3, CF2=CFO(CF2)3O(CF2)2CF3、 CF2=CFO(CF2CF(CF3)O)2(CF2)2CF3, CF2=CFOCF2CF(CF3)O(CF2)2CF3, CF2=CFOCF2CF=CF2, CF2=CFO(CF2)2CF=CF2, etc.
[0033] Specific examples of the monomer (a4) include the following compounds. CF2=CFO(CF2)3CO2CH3、 CF2=CFOCF2CF(CF3)O(CF2)3CO2CH3, CF2=CFOCF2CF(CF3)O(CF2)2SO2F, etc.
[0034] Specific examples of the monomer (a5) include perfluoro(2,2-dimethyl-1,3-dioxole), 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxole, and perfluoro(2-methylene-4-methyl-1,3-dioxolane).
[0035] Examples of the monomer containing no fluorine atom include the following monomers (b1) to (b4). Monomer (b1): olefins, Monomer (b2): vinyl esters, Monomer (b3): vinyl ethers, Monomer (b4): unsaturated acid anhydride. Specific examples of the monomer (b1) include propylene and isobutylene. Specific examples of the monomer (b2) include vinyl acetate and the like. Specific examples of the monomer (b3) include ethyl vinyl ether, butyl vinyl ether, cyclohexyl vinyl ether, and hydroxybutyl vinyl ether.
[0036] Specific examples of the monomer (b4) include maleic anhydride, itaconic anhydride, citraconic anhydride, and 5-norbornene-2,3-dicarboxylic anhydride.
[0037] As the third monomer, monomer (a2), HFP, PPVE, and vinyl acetate are preferred from the perspective of easy adjustment of crystallinity and excellent tensile strength and elongation at high temperatures (particularly around 180°C). HFP, PPVE, CF3CF2CH=CH2, and PFBE are more preferred, and PFBE is even more preferred.
[0038] The molar ratio of TFE unit to E unit (TFE unit / E unit) in ETFE is preferably 80 / 20 to 40 / 60, more preferably 70 / 30 to 45 / 55, and particularly preferably 65 / 35 to 50 / 50. When the TFE unit / E unit is within the above range, ETFE has excellent heat resistance and mechanical strength. The ratio of the units based on the third monomer in ETFE to the total of all units constituting ETFE (100 mol%) is preferably 0.01 to 20 mol%, more preferably 0.10 to 15 mol%, and particularly preferably 0.20 to 10 mol%. When the ratio of the units based on the third monomer is within the above range, ETFE has excellent heat resistance and mechanical strength.
[0039] When the units derived from the third monomer include PFBE units, the ratio of the PFBE units relative to the total of all units constituting ETFE (100 mol%) is preferably 0.5 to 4.0 mol%, more preferably 0.7 to 3.6 mol%, and particularly preferably 1.0 to 3.6 mol%. When the ratio of the PFBE units is within this range, the tensile strength and elongation of the release film at high temperatures (particularly around 180°C) are improved.
[0040] The melting point of ETFE is preferably 190° C. or higher, more preferably 200° C. or higher, further preferably 210° C. or higher, and particularly preferably 220° C. or higher. The upper limit of the melting point of ETFE is not particularly limited, but is, for example, 270°C. When the melting point of ETFE is within such a range, the release film tends to be excellent in tensile strength and elongation at high temperatures (particularly around 180° C.). The "melting point" refers to the temperature corresponding to the maximum of the melting peak measured by differential scanning calorimetry (DSC). The melt flow rate (MFR) of ETFE is preferably 2 to 40 g / 10 minutes, more preferably 5 to 30 g / 10 minutes, and particularly preferably 5 to 20 g / 10 minutes. When the MFR of ETFE is within such a range, the release film has a large elongation at high temperatures and is excellent in conformity to a mold. The MFR of ETFE is a value measured under conditions of a load of 49 N and 297° C. in accordance with ASTM D3159.
[0041] The base material may further contain components other than the resin. Examples of other components include lubricants, antioxidants, antistatic agents, plasticizers, and mold release agents. From the perspective of preventing mold contamination, the content of other components in the substrate is preferably 5% by mass or less, more preferably 1% by mass or less, further preferably 0.5% by mass, and particularly preferably 0% by mass (no content).
[0042] Regarding the surface of the substrate, from the perspective of making damage to the surface of the semiconductor package obtained using the release film less noticeable, thus improving the appearance quality, and suppressing wrinkles on the mold surface of the film during the semiconductor package sealing process, the arithmetic mean height Sa of at least one surface of the substrate is preferably 0.9 μm or greater, more preferably 1.1 μm or greater, and even more preferably 1.2 μm or greater. From the perspective of laser marking visibility on the semiconductor package surface, the arithmetic mean height Sa of at least one surface of the substrate is preferably 2.7 μm or less, more preferably 2.6 μm or less, and even more preferably 2.5 μm or less. From the perspective of laser marking recognizability and making the resin flow marks (flow marks) on the surface of the semiconductor package and the damage on the surface of the package inconspicuous, that is, improving the appearance quality, the arithmetic mean height Sa of the substrate surface on the first side (antistatic layer side) is preferably above 0.05 μm, more preferably above 0.9 μm, further preferably above 1.2 μm, particularly preferably above 1.4 μm, and extremely preferably above 1.5 μm. From the viewpoint of laser marking visibility, the arithmetic mean height Sa of the substrate surface on the first surface side is preferably 2.7 μm or less, more preferably 2.6 μm or less, and further preferably 2.5 μm or less.
[0043] In addition, from the perspective of suppressing wrinkles of the film on the mold surface during the sealing process of the semiconductor package and from the perspective of mold releasability on the mold, the arithmetic mean height Sa of the substrate surface on the release layer side surface of the release film (the surface of the release film on the side of the substrate with respect to the release layer, hereinafter also referred to as the "second surface") is preferably greater than 0.03 μm, more preferably greater than 0.05 μm, and further preferably greater than 0.1 μm. From the perspective of suppressing wrinkles of the film on the mold surface during the sealing process of the semiconductor package, the arithmetic mean height Sa of the substrate surface on the second side is preferably 0.9 μm or more, more preferably 1.2 μm or more, further preferably 1.3 μm or more, and particularly preferably 1.5 μm or more. From the perspective of laser marking visibility on the surface of the semiconductor package, the arithmetic mean height Sa of the substrate surface on the second side is preferably 2.7 μm or less, more preferably 2.6 μm or less, and further preferably 2.5 μm or less. If the arithmetic mean height Sa of the substrate surface on the second side is below the upper limit, the shape of the substrate surface on the second side is less likely to affect the surface of the semiconductor package. Furthermore, the arithmetic mean height Sa of the substrate surface on the second surface side may be less than 0.03 μm, may be 0.02 μm or less, and may be a mirror surface.
[0044] The arithmetic mean height Sa of the substrate surface can be measured after removing the release layer, the antistatic layer, and other layers from the release film using methyl ethyl ketone.
[0045] In a substrate, the surface shape having an arithmetic mean height Sa of 0.9 μm or greater may be a shape in which at least one of the plurality of protrusions and recesses is randomly distributed, or a shape in which at least one of the plurality of protrusions and recesses is regularly arranged. The shapes of the plurality of protrusions may be the same or different. Furthermore, the sizes of the plurality of protrusions may be the same or different. The sizes of the plurality of recesses may be the same or different.
[0046] Examples of the convex portions include long convex portions extending on the surface of the release film and scattered protrusions, and examples of the concave portions include long grooves extending on the surface of the release film and scattered holes. Examples of the shape of the convex shape or groove include straight lines, curves, and bends. Multiple convex shapes or grooves may be present in parallel on the surface of the release film to form a stripe shape. Examples of the cross-sectional shape of the convex shape or groove in a direction perpendicular to the longitudinal direction include polygons such as triangles (V-shaped), and semicircles. Examples of the shape of the protrusion or hole include polygonal pyramids such as triangular pyramids, quadrangular pyramids, and hexagonal pyramids, circular cones, hemispherical shapes, polyhedrons, and various other irregular shapes.
[0047] The method for producing a substrate having a surface with an arithmetic mean height Sa of 0.9 μm or greater is not particularly limited, and known production methods can be used. For example, a method in which the concavo-convex portions of the original mold are transferred to the surface of a resin film by heat processing can be used. From the perspective of productivity, the following methods (i) and (ii) are preferred, with method (ii) being particularly preferred.
[0048] (i) A method in which a resin film is passed between two rollers to continuously transfer the concavo-convex patterns formed on the roller surfaces to the resin film. (ii) A method in which a resin extruded from a die of an extruder is passed between two rolls, and the resin is formed into a film shape while the concavities and convexities formed on the roll surfaces are continuously transferred to the surface of the film-like resin.
[0049] One of the two rollers is a roller with a concavo-convex surface (hereinafter also referred to as a die roller) and the other is a roller without concavo-convex, thereby manufacturing a substrate with concavo-convex on one side. Both rollers are die rollers, thereby manufacturing a substrate with concavo-convex on both sides. In addition, at least one of the two rollers usually has the function of pressurizing the resin film, also known as a pressure roller. When using a roller without a concavo-convex surface, the roller without a concavo-convex surface is usually a cooling roller. When both rollers are die rollers, one of them is a cooling roller. In addition, a roller without a concavo-convex surface also refers to a roller having a surface that can actually form a smooth surface.
[0050] The irregularities on the mold roller surface are the inverse of the specific irregularities on the substrate, and are the same as the irregularities formed on the surface of the resin sealing portion of the semiconductor package. Examples of a method for forming irregularities on the surface of the mold roll include cutting and etching. Furthermore, in the case of rubber rolls, particles can be added to the rubber sheet wound around the surface to create a molded roll with uneven surfaces. In this case, the depth-wise roughness (Sa) can be adjusted by adjusting the size of the particles added to the rubber sheet. The same method can be used to adjust Sa for resin rolls.
[0051] In methods (i) and (ii), in addition to the unevenness of the roller surface, the arithmetic mean height Sa of the substrate surface can also be adjusted by adjusting the processing speed, the melt flow rate (MFR) of the substrate resin, the roller pressure, the distance between the mold and the roller, etc.
[0052] The average thickness of the substrate is preferably 35 to 100 μm, more preferably 35 to 75 μm. When the substrate thickness is 35 μm or greater, the release film has excellent releasability. When the substrate thickness is 75 μm or less, the release film can be easily deformed and has excellent mold conformability. When the substrate thickness is 100 μm or less, the release film is easy to handle (e.g., roll-to-roll operation), and wrinkles are less likely to form when the release film is pulled and arranged to cover the mold cavity.
[0053] The average thickness of the substrate is measured according to ISO 4591:1992 (JIS K7130:1999, Method B1, Thickness Measurement by Mass of a Sample Collected from a Plastic Film or Sheet). In this case, the average thickness of the substrate can be measured after removing the release layer, antistatic layer, and other layers from the release film using methyl ethyl ketone.
[0054] (Antistatic layer) The antistatic layer is not particularly limited as long as it is made of a material having an antistatic function. The antistatic layer preferably contains an antistatic agent. Examples of the antistatic agent include ionic liquids, conductive polymers, metal ion conductive salts, and conductive metal oxides. Conductive polymers are polymers in which electrons move and diffuse through the polymer skeleton (polymer backbone). Examples of conductive polymers include polyaniline polymers, polyacetylene polymers, polyparaphenylene polymers, polypyrrole polymers, polythiophene polymers, and polyvinylcarbazole polymers. Examples of the metal ion conductive salt include lithium salt compounds. Examples of the conductive metal oxide include tin oxide, tin-doped indium oxide, antimony-doped tin oxide, phosphorus-doped tin oxide, zinc antimonate, and antimony oxide.
[0055] The antistatic layer preferably contains a resin binder. When the antistatic layer contains a resin binder and an antistatic agent, the antistatic agent is preferably dispersed in the resin binder. As a resin adhesive, it is preferred to have heat resistance that can withstand the heat (e.g., 180°C) during the sealing process, and examples thereof include acrylic resins, silicone resins, urethane resins, polyester resins, polyamide resins, vinyl acetate resins, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, trifluorochloroethylene-vinyl alcohol copolymers, and tetrafluoroethylene-vinyl alcohol copolymers.
[0056] The resin binder may be cross-linked. If the resin binder is cross-linked, it has better heat resistance than the uncross-linked resin binder. Examples of such resin binders include carboxyl-containing (meth) acrylic polymers and hydroxyl-containing acrylic polymers. Crosslinking agents include polyfunctional aziridine compounds and polyfunctional epoxy compounds in the case of carboxyl-containing acrylic polymers, and polyfunctional isocyanate compounds in the case of hydroxyl-containing acrylic polymers.
[0057] The surface resistivity of the antistatic layer is preferably 1×10 10 Ω / □ or less, more preferably 1×10 9 Ω / □ or less. The lower limit of the surface resistivity of the antistatic layer is not particularly limited and can be 1×10 7 Ω / □ or more. The content of the antistatic agent in the antistatic layer is appropriately set so that the surface resistivity of the antistatic layer is within the above range.
[0058] From the viewpoint of reducing the surface resistivity of the first surface of the release film while maintaining the releasability, the average thickness of the antistatic layer is preferably 0.05 to 3 μm, more preferably 0.05 to 2 μm. The method for measuring the average thickness of the antistatic layer and the average thickness of the release layer described later is not particularly limited. For example, the release layer and the antistatic layer are removed from the release film respectively using methyl ethyl ketone, and the mass of each layer before and after removal is measured. The average thickness of the antistatic layer and the average thickness of the release layer described later can be calculated using the reduced mass and the density of each layer. In addition, the average thickness of the antistatic layer and the average thickness of the release layer described later can be obtained by cross-sectional observation of the release film using a focused ion beam scanning electron microscope (FIB-SEM). In FIB-SEM, the boundary of the layer can be determined by the difference in interlayer contrast, thereby measuring the thickness of each layer. This measurement is performed at random at 30 locations, and when the surface is concave and convex, at least 30 locations between the concave and convex parts are confirmed. By averaging the measurement results, the average thickness of each layer can be obtained. In addition, when there is no difference in contrast between the antistatic layer and the release layer when observing the cross-section through FIB-SEM and the boundary of the layer cannot be determined, a scanning transmission electron microscope (STEM-EDX) can be used to determine the boundary of the layer by the presence or absence of characteristic elements in the antistatic layer (especially the antistatic agent contained in the antistatic layer) and the release layer.
[0059] The method for forming the antistatic layer is not particularly limited, but preferably the antistatic layer composition is applied to one surface of the substrate and dried. Various known wet coating methods can be used for the coating, including gravure coating, die coating, and rod coating. The drying temperature and time are appropriately adjusted according to the type and content of the liquid medium.
[0060] In addition to the antistatic agent, the antistatic layer composition may also contain other components. Examples of other components include liquid media such as solvents and water. The solid content of the antistatic layer composition is appropriately adjusted according to the coating properties. Before applying the antistatic layer composition, the surface of the substrate is preferably subjected to a corona treatment from the viewpoint of improving wettability. The corona treatment is preferably performed so that the wetting tension based on ISO 8296:1987 (JIS K6768:1999) is 40 mN / m or more.
[0061] (Release layer) The material of the release layer is not particularly limited as long as it is a layer having release properties. The release layer may or may not have adhesive properties. The release layer preferably contains a reaction-cured product of a hydroxyl group-containing acrylic polymer and a polyfunctional isocyanate compound.
[0062] The hydroxyl group of the hydroxyl group-containing acrylic polymer is a crosslinking functional group that reacts with the isocyanate group in the polyfunctional isocyanate compound. The hydroxyl value of the hydroxyl group-containing acrylic polymer is preferably 1 to 100 mg KOH / g, particularly preferably 29 to 100 mg KOH / g. The hydroxyl value is measured according to the method specified in JIS K0070:1992.
[0063] The hydroxyl group-containing acrylic polymer may or may not have a carboxyl group. Like the hydroxyl group, the carboxyl group is a crosslinking functional group that reacts with the isocyanate group in the polyfunctional isocyanate compound. The acid value of the hydroxyl group-containing acrylic polymer is preferably 0 to 100 mg KOH / g, particularly preferably 0 to 30 mg KOH / g. Similar to the hydroxyl value, the acid value is measured according to the method specified in JIS K0070:1992.
[0064] The crosslinking functional group equivalent weight (the total equivalent weight of the hydroxyl group and the carboxyl group) of the hydroxyl group-containing acrylic polymer is 2,000 g / mol or less, preferably 500 to 2,000 g / mol, and particularly preferably 600 to 1,000 g / mol. The “total equivalent weight of hydroxyl groups and carboxyl groups” refers to the mass of the hydroxyl group-containing acrylic polymer when the total amount of hydroxyl groups and carboxyl groups is 1 mol.
[0065] The crosslinking functional group equivalent weight is equivalent to the molecular weight between crosslinking points and is a physical property value that determines the elastic modulus (elastic modulus of the reaction cured product) after crosslinking. When the crosslinking functional group equivalent weight is 2,000 g / mol or less, the elastic modulus of the reaction cured product is sufficiently high, and the release layer has excellent releasability from the resin seal and peelability from the semiconductor chip, source electrode, or sealing glass. In addition, when the crosslinking functional group equivalent weight is 2,000 g / mol or less, its transfer to the resin seal (residual adhesive) is suppressed.
[0066] The mass average molecular weight (Mw) of the hydroxyl group-containing acrylic polymer is preferably 100,000 to 1.2 million, more preferably 200,000 to 1,000,000, and particularly preferably 200,000 to 700,000. A mass average molecular weight of 100,000 or greater provides superior releasability from the resin seal and re-peelability from the semiconductor chip, source electrode, or sealing glass. A mass average molecular weight of 1.2 million or less provides superior adhesion to the semiconductor chip, source electrode, or sealing glass. The mass average molecular weight of the hydroxyl group-containing acrylic polymer is a polystyrene-equivalent value obtained by measuring by gel permeation chromatography using a calibration curve prepared using standard polystyrene samples with known molecular weights.
[0067] The glass transition temperature (Tg) of the hydroxyl group-containing acrylic polymer is preferably 20° C. or lower, particularly preferably 0° C. or lower. When Tg is at least the lower limit of the above range, the release layer exhibits sufficient flexibility even at low temperatures and is easily peeled from the substrate. The lower limit of Tg is not particularly limited, but is preferably -60°C or higher within the above-mentioned molecular weight range. In the present disclosure, Tg refers to the midpoint glass transition temperature measured by differential scanning calorimetry (DSC).
[0068] The polyfunctional isocyanate compound is a compound having two or more isocyanate groups, and preferably a compound having 3 to 10 isocyanate groups. Examples of the polyfunctional isocyanate compound include hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), naphthalene diisocyanate (NDI), dimethyldiphenyl diisocyanate (TODI), isophorone diisocyanate (IPDI), xylylenediisocyanate (XDI), triphenylmethane triisocyanate, and triphenylthiophosphate isocyanate. Examples include isocyanurate forms (trimers) and biuret forms of these polyfunctional isocyanate compounds, and adducts of these polyfunctional isocyanate compounds with polyol compounds. It is preferred that the polyfunctional isocyanate compound has an isocyanurate ring because the planarity of the ring structure allows the reaction cured product (release layer) to exhibit a high elastic modulus. Examples of the polyfunctional isocyanate compound having an isocyanurate ring include an isocyanurate form of HDI (isocyanurate-type HDI), an isocyanurate form of TDI (isocyanurate-type TDI), and an isocyanurate form of MDI (isocyanurate-type MDI).
[0069] The release layer may contain other components. Examples of other components include cross-linking catalysts (eg, amines, metal compounds, acids, etc.), reinforcing fillers, coloring dyes, pigments, antistatic agents, and the like. As the antistatic agent, those exemplified for the antistatic layer can be used.
[0070] When a multifunctional isocyanate compound is used as the crosslinking agent, the crosslinking catalyst may be any substance that can catalyze the reaction (urethanization reaction) between the hydroxyl-containing acrylic copolymer and the crosslinking agent. Conventional urethanization catalysts can be used, and examples thereof include amine compounds such as tertiary amines, organotin compounds, organolead compounds, and organozinc compounds, among others. Examples of tertiary amines include trialkylamines, N,N,N',N'-tetraalkyldiamines, N,N-dialkylaminoalcohols, triethylenediamine, morpholine derivatives, and piperazine derivatives. Examples of organotin compounds include dialkyltin oxides, dialkyltin fatty acid salts, and stannous fatty acid salts.
[0071] As the crosslinking catalyst, an organotin compound is preferred, with dioctyltin oxide, dioctyltin dilaurate, dibutyltin laurate, and dibutyltin dilaurate being particularly preferred. Alternatively, a dialkyltin acetylacetonate complex catalyst having a structure in which one dialkyltin atom is coordinated with two molecules of acetylacetone, synthesized by reacting a dialkyltin ester with acetylacetone in a solvent, may be used. The amount of the crosslinking catalyst used is preferably 0.01 to 0.5 parts by mass relative to 100 parts by mass of the hydroxyl group-containing acrylic polymer.
[0072] The release layer may contain particles. The particles can be used to adjust the fraction (Φ) of particles present in the range of 10 to 35° on the first surface of the release film. In addition, the release layer may further contain particles on the basis of using a substrate having a concavo-convex structure on the surface to adjust the fraction (Φ) of particles present in the range of 10 to 35° on the first surface of the release film. In addition, when using a substrate having a concavo-convex structure on the surface, the release layer may not contain particles.
[0073] The material of the particles contained in the release layer is not particularly limited, and for example, they may be organic particles or inorganic particles. Examples of the organic particles include acrylic resin particles, polyolefin resin particles, polystyrene resin particles, polyacrylonitrile resin particles, and silicone resin particles. Examples of the inorganic particles include silicon oxide particles and aluminum oxide particles.
[0074] The average particle size of the particles is preferably 2.0 μm or larger, more preferably 2.5 μm or larger, and further preferably 3.0 μm or larger. In this case, the resin flow marks (flow marks) of the formed resin sealing portion can be made less noticeable. The average particle size of the particles is preferably 10 μm or less, more preferably 7.5 μm or less, and even more preferably 5 μm or less. In this case, the particles can be easily prevented from detaching from the release layer.
[0075] When the release layer contains particles, the particle content in the release layer is preferably 3.0% by volume or more, more preferably 3.9% by volume or more, and even more preferably 5.0% by volume or more, from the perspective of making the resin flow marks (flow marks) inconspicuous in the formed resin seal. From the perspective of easily suppressing the detachment of particles from the release layer, the particle content in the release layer is preferably 25% by volume or less, more preferably 20% by volume or less, and even more preferably 16.5% by volume or less. In addition, when using a substrate having a concave-convex structure on the surface, from the viewpoint of easily suppressing the detachment of particles from the release layer, the content of particles in the release layer is preferably 16.5% by volume or less, more preferably 10% by volume or less, further preferably 4.9% by volume or less, and can be 0% by volume, i.e., containing no particles.
[0076] The content of particles can be calculated as the ratio of resin particles per unit volume by observing a cross section of the release layer using a scanning electron microscope (SEM), for example. Specifically, the content can be calculated by the following method. First, a cross-section of the target release layer is observed using a SEM, and the number and particle size of the resin particles contained within a random area of the cross-section (hereinafter referred to as the "target area") are measured. Furthermore, a random volume (hereinafter referred to as the "target volume") is set based on the target area, and the number of resin particles contained within the target volume is calculated. Furthermore, the volume per resin particle is calculated based on the particle size of the resin particles. The total volume of the resin particles contained within the target volume is calculated from the calculated number of resin particles and the volume per resin particle. The volume content of the resin particles in the target release layer is calculated by dividing the total volume of the resin particles by the target volume.
[0077] From the perspective of the release properties of the release film, the average thickness of the release layer is greater than 0.1 μm, preferably 0.15 μm or greater, more preferably 0.17 μm or greater, and further preferably 0.2 μm or greater. From the viewpoint of the antistatic properties of the release film, the thickness of the release layer is preferably 2.3 μm or less, more preferably 2.2 μm or less, and even more preferably 2.1 μm or less. When the thickness of the release layer is 2.3 μm or less, the antistatic properties are more excellent.
[0078] As a method for forming the release layer, a method of applying a release layer composition comprising the components of the release layer and a liquid medium onto the antistatic layer and drying the composition is preferred. Various known wet coating methods can be used, including gravure coating, die coating, and rod coating. The drying temperature and time are appropriately adjusted depending on the type and content of the liquid medium.
[0079] (Other layers) The release film may further comprise other layers. The other layers may be disposed between the substrate layer and the antistatic layer or between the antistatic layer and the release layer, may be disposed on the side of the substrate layer opposite to the antistatic layer, or may be disposed on the side of the release layer opposite to the antistatic layer. For example, the other layers may be the first surface of the release film. Examples of other layers include a gas barrier layer and a coloring layer. These layers may be used alone or in combination of two or more. The average thickness of each of the other layers is preferably 0.05 to 3 μm, more preferably 0.05 to 2 μm.
[0080] (Various physical properties of release film) The arithmetic mean height Sa of the first surface of the release film is preferably 1.0 μm or more, more preferably 1.1 μm or more. In this case, the resin flow marks (flow marks) of the formed resin sealing portion are less noticeable, which is preferable. Furthermore, when the release layer does not contain particles, the arithmetic mean height Sa of the first surface of the release film is preferably 2.3 μm or less, more preferably 2.2 μm or less, and even more preferably 2.1 μm or less. In this case, the laser marking visibility of the surface of the semiconductor package formed using the release film is further improved. When the release layer contains particles, the arithmetic mean height Sa of the first surface of the release film is preferably 3.0 μm or less, more preferably 2.9 μm or less, and even more preferably 2.7 μm or less. In this case, laser marking visibility is further improved.
[0081] The surface resistivity of the first surface of the release film is preferably 1×10 11 Ω / □ or less, more preferably 2×10 10 Ω / □ or less. In this case, the damage of the semiconductor chip caused by discharge during peeling can be effectively prevented. The lower limit of the surface resistivity of the first surface of the release film is not particularly limited and can be within 1×10 7 Ω / □ or more. The surface resistivity was measured in accordance with the double-ring electrode method (double-ring electrode method) of IEC 60093.
[0082] The electrostatic voltage of the first surface of the release film is preferably |0 to 50| V, more preferably |0 to 30| V, and further preferably |0 to 25| V. The electrostatic voltage is measured with a surface potentiometer.
[0083] <Method for manufacturing a semiconductor package> The present invention relates to a method for manufacturing a semiconductor package having a semiconductor element and a resin sealing portion formed by a curable resin that seals the semiconductor element. The method comprises: placing a substrate having the semiconductor element in a mold cavity; placing a release film having a release layer, an antistatic layer, and a base material on a surface of the mold cavity where the substrate is not arranged, with the surface of the release layer facing the space in the mold cavity; filling the mold cavity with the curable resin; and curing the curable resin while it is in contact with the release film to form a resin sealing portion that seals the semiconductor element.
[0084] In addition to using the release film disclosed herein, the manufacturing method of the semiconductor package disclosed herein can employ known manufacturing methods. For example, compression molding and transfer molding are examples of methods for forming the resin seal portion, and the apparatus used in these methods can be a known compression molding apparatus or transfer molding apparatus. The manufacturing conditions can also be the same as those used in known semiconductor package manufacturing methods. The following describes compression molding and transfer molding as representative examples with reference to the accompanying drawings. However, the semiconductor package manufacturing method disclosed herein is not limited to these drawings. Furthermore, the following description shows a so-called MAP-BGA shaped semiconductor package as an example of a semiconductor package, but the shape of the semiconductor package is not limited to this.
[0085] Figures 3-4 Shown is a cross-sectional view schematically illustrating the outline of the compression molding method. Figure 3 The compression molding method shown uses a mold comprising a fixed upper mold 20, a cavity bottom member 22, and a frame-shaped movable lower mold 24 disposed around the periphery of the cavity bottom member 22. The fixed upper mold 20 is provided with vacuum vents (not shown) that draw air between the substrate 10 and the fixed upper mold 20, thereby allowing the substrate 10 to be attracted to the fixed upper mold 20. Furthermore, the cavity bottom member 22 is provided with vacuum vents (not shown) that draw air between the release film 30 and the cavity bottom member 22, thereby allowing the release film 30 to be attracted to the cavity bottom member 22.
[0086] A release film 30 is placed on the movable lower mold 24 so as to cover the upper surface of the cavity bottom member 22. The release film 30 is placed with its first surface facing upward (in the opposite direction to the cavity bottom member 22). The release film 30 is fed out by a feed roll (not shown) and taken up by a take-up roll (not shown). The release film 30 is drawn out by the feed roll and the take-up roll and is placed on the movable lower mold 24 in a stretched state.
[0087] Furthermore, vacuum is drawn through the vacuum exhaust port (not shown) of the cavity bottom member 22, reducing the pressure in the space between the upper surface of the cavity bottom member 22 and the release film 30. This stretches and deforms the release film 30, causing it to be vacuum-adsorbed onto the upper surface of the cavity bottom member 22. Furthermore, the frame-shaped movable lower mold 24 disposed around the periphery of the cavity bottom member 22 is tightened, stretching the release film 30 in all directions and keeping it taut. In addition, depending on the strength and thickness of the release film 30 under high temperature environment and the shape of the concave portion formed by the upper surface of the cavity bottom member 22 and the inner side surface of the movable lower mold 24, the release film 30 may not necessarily be in close contact with the cavity surface. Figure 3 As shown, a small amount of space remains between the release film 30 and the cavity surface.
[0088] like Figure 3 As shown, an appropriate amount of curable resin 40 is filled onto the release film 30 in the cavity 26 by an applicator (not shown). Furthermore, vacuum is drawn through a vacuum exhaust port (not shown) of the fixed upper mold 20 , so that the substrate 10 with the plurality of semiconductor chips 12 mounted thereon is vacuum-adsorbed onto the lower surface of the fixed upper mold 20 . Various curable resins used in the production of semiconductor packages can be used as the curable resin 40. Thermosetting resins such as epoxy resins and silicone resins are preferred, and epoxy resins are particularly preferred.
[0089] Afterwards, if Figure 4 As shown, in a state where the release film 30 in the cavity 26 is filled with the curable resin 40 , the cavity bottom surface member 22 and the movable lower mold 24 are raised and clamped with the fixed upper mold 20 . Afterwards, if Figure 5 As shown, while only the cavity bottom member 22 is raised, the mold is heated to cure the curable resin 40 and seal the semiconductor chip 12 .
[0090] The pressure from the elevated cavity bottom member 22 further squeezes the curable resin 40 filled in the cavity 26 toward the cavity surface. This stretches and deforms the release film 30, causing it to adhere tightly to the cavity surface. This forms a resin seal corresponding to the shape of the cavity 26. The unevenness of the first surface of the release film 30 is then transferred to the surface of the resin seal.
[0091] Then, the fixed upper mold 20, the cavity bottom member 22, and the movable lower mold 24 are opened to take out the assembled sealed body. The monolithic sealed body is demolded, and the used portion of the release film 30 is fed to a take-up roll (not shown), while the unused portion of the release film 30 is fed out from a feed roll (not shown).
[0092] The substrate 10 and the resin sealing portion of the packaged sealed body removed from the mold are cut to separate (individualize) the plurality of semiconductor chips 12, thereby obtaining a singulated sealed body having the substrate 10, at least one semiconductor chip 12, and the resin sealing portion 14 sealing the semiconductor chip 12. Singulation can be performed by a known method, an example of which is a dicing method.
[0093] Arbitrary information is printed on the upper surface (the surface in contact with the first surface of the release film 30 ) of the resin sealing portion of the obtained individual sealed body by laser marking, thereby obtaining a semiconductor package. When characters are printed on a semiconductor package manufactured using the release film of the present disclosure using laser marking, the characters have excellent legibility.
[0094] Figures 6-11 Shown is a cross-sectional view schematically illustrating the outline of the transfer molding method. Figure 6In the transfer molding method shown, a mold having an upper mold 50 and a lower mold 52 is used. The upper mold 50 is formed with a cavity 54 having a shape corresponding to the shape of the resin sealing portion 14, and a concave resin introduction portion 60 for guiding the curable resin 40 into the cavity 54. The lower mold 52 is formed with a substrate placement portion 58 for placing the substrate 10 on which the semiconductor chip 12 is mounted, and a resin placement portion 62 for placing the curable resin 40. Furthermore, a plunger 64 is provided in the resin placement portion 62 for extruding the curable resin 40 toward the resin introduction portion 60 of the upper mold 50.
[0095] like Figure 7 As shown, the release film 30 is arranged to cover the cavity 54 of the upper mold 50. The release film 30 is preferably arranged to cover the entire cavity 54 and the resin introduction portion 60. The release film 30 is pulled by a pay-out roller (not shown) and a take-up roller (not shown) and arranged in a stretched state to cover the cavity 54 of the upper mold 50.
[0096] Then, if Figure 8 As shown, by vacuuming the groove (not shown) formed on the outside of the mold cavity 54 of the upper mold 50, the space between the release film 30 and the mold cavity surface 56, and the space between the release film 30 and the inner wall of the resin inlet part 60 are reduced in pressure, and the release film 30 is stretched and deformed, thereby being vacuum adsorbed to the mold cavity surface 56 of the upper mold 50.
[0097] Afterwards, if Figure 9 As shown, the substrate 10 on which the plurality of semiconductor chips 12 are mounted is placed in the substrate placement portion 58, and the upper mold 50 and the lower mold 52 are clamped together to arrange the plurality of semiconductor chips 12 at predetermined positions within the mold cavity 54. Furthermore, a curable resin 40 is preliminarily placed on the plunger 64 of the resin placement portion 62. Examples of the curable resin 40 include the same resins as those mentioned in the compression molding method.
[0098] Then, if Figure 10 As shown, plunger 64 of lower mold 52 is pushed upward to fill cavity 54 with curable resin 40 through resin introduction portion 60. The mold is then heated to cure curable resin 40, sealing semiconductor chips 12 to form resin sealing portion 14. By filling cavity 54 with curable resin 40, release film 30 is further pushed toward cavity surface 56 by resin pressure, and deformed by stretching to adhere to cavity surface 56. Thus, resin sealing portion 14 having a shape corresponding to that of cavity 54 is formed.
[0099] like Figure 11As shown, the monolithic sealed body 1A is removed from the mold. At this point, the cured product 19 formed by curing the curable resin 40 within the resin inlet 60 is removed from the mold together with the monolithic sealed body 1A while remaining attached to the resin sealing portion 14 of the monolithic sealed body 1A. Therefore, the cured product 19 attached to the removed monolithic sealed body 1A is removed, resulting in the monolithic sealed body 1A.
[0100] The substrate 10 and the resin sealing portion 14 of the obtained monolithic sealed body 1A are diced to separate the semiconductor chips 12 (individualized), thereby obtaining individualized sealed bodies having the substrate 10, at least one semiconductor chip 12, and the resin sealing portion 14 sealing the semiconductor chip 12. The subsequent steps are the same as those of the compression molding method. The method for manufacturing a semiconductor package using the release film of the present disclosure can form a semiconductor package surface having excellent laser marking visibility.
[0101] Semiconductor packages The semiconductor package manufactured using the release film of the present invention and the method for manufacturing the semiconductor package of the present invention can be any semiconductor package manufactured by whole-package sealing and singulation, and examples include semiconductor packages whose sealing method is MAP (Moldied Array Packaging) method or WL (Wafer Level Packaging) method. A semiconductor package manufactured using the release film of the present disclosure has a surface with excellent laser marking visibility. Example
[0102] The present invention will be described in detail below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. Among Examples 1 to 27, Examples 1 to 13 and 23 to 27 are embodiments, and Examples 14 to 22 are comparative examples. The evaluation methods and materials used in each case are shown below.
[0103] [Evaluation Method] (thickness) The average thickness (μm) of the substrate was measured in accordance with ISO 4591:1992 (Method B1 of JIS K7130:1999, a thickness measurement method using a mass method of a sample collected from a plastic film or sheet). Each layer was removed from the release film using methyl ethyl ketone, and the mass of each layer before and after removal was measured. The average thickness (μm) of the antistatic layer and the release layer was determined using the mass reduction and the density of each layer.
[0104] (Arithmetic mean height Sa) The arithmetic mean height (Sa) of both surfaces of the substrate and the first surface of the release film (the surface in contact with the curable resin) was measured in accordance with JIS B0601:2013 (ISO 4287:1997, Amd. 1:2009). Measurements were performed using an Olympus laser microscope (LEXT OLS 4000) at an ambient temperature of 23-25°C. The sample was attached to a metal substrate to eliminate the influence of the sample's own significant tilt. The main laser microscope settings are as follows.
[0105] Objective lens: MPLAPON50LEXT (magnification: 50x, numerical aperture: 0.95, immersion type: air, mechanical barrel length: ∞, cover glass thickness: 0, field of view: FN18) Optical zoom ratio: 1x Scanning mode: XYZ high precision Captured image size [number of pixels]: 259 μm horizontally × 259 μm vertically [1024 × 1024] DIC: Off Multi-layer: Off Laser intensity: 100 Bias: 0 Confocal level: 0 Beam diameter aperture: Off Image averaging: 1 time Noise reduction: On Uneven brightness correction: On Optical noise filtering: On Cutoff: None (λc, λs, λf are all absent) Filtering: Gaussian filtering Noise removal: pre-measurement processing Tilt correction: Not implemented
[0106] (Surface angular distribution) The surface shape of the first surface of the release film was measured under the same conditions as for the measurement of the arithmetic mean height Sa using a laser microscope (LEXT OLS 4000) manufactured by Olympus Corporation in accordance with ISO-25178-2: 2012. The measurement position was varied and the number of measurements was 12. Using the MATLAB (registered trademark) R2022b surfnorm function, the X-, Y-, and Z-coordinate (height) data for each point, obtained at 0.25 μm intervals, were used to determine the normal vector of the concave-convex surface at each point. The angle (θ) formed between the normal vector of the concave-convex surface and the normal to the main surface of the release film was calculated and histized at 0.1° intervals to determine the surface angle distribution. In the surface angle distribution, the percentage of the area occupied by angles (θ) within the range of 10 to 35° relative to the total area of all angles from 0 to 90° was calculated as the presence fraction (Φ) within the range of 10 to 35°.
[0107] (Surface resistivity) The surface resistivity (Ω / □) of the first surface (the surface in contact with the curable resin) of the release film was measured according to the double-ring electrode method of IEC 60093. An ultra-high resistance meter R8340 (Advantec Co., Ltd.) was used as the measuring instrument, and a resistance chamber 12704A was used as the electrode. The measurement was performed under the conditions of an applied voltage of 500 V and an application time of 1 minute.
[0108] (Mold release) A 13 cm x 13 cm, 100 μm thick aluminum foil (AIN30P according to JISH 4000:2006) was placed on a 13 cm x 13 cm first stainless steel plate. A 10 cm x 12 cm, 125 μm thick polyimide film (UPILEX 125S, manufactured by Ube Industries, Ltd.) with an 8 cm x 10 cm cutout was placed on top as a spacer. Furthermore, an appropriate amount of semiconductor encapsulation epoxy resin (Sumikon EME G770H F type ver. GR, manufactured by Sumitomo Bakelite Co., Ltd.) was dispersed into the cutouts of the polyimide film as a curable resin. A release film, previously cut to a 13 cm x 13 cm size and freed from static electricity, was placed on top of the film so that the first surface came into contact with the curable resin. Finally, a 13 cm x 13 cm second stainless steel plate was placed on top.
[0109] The sample produced according to the above steps was pressed in a press at 180°C, 1 MPa, and 3 minutes. After removal from the press, the entire sample was placed on a hot plate at 180°C. The second stainless steel plate was removed, and the release film was manually peeled off over 5 seconds. The peelability was evaluated using the following criteria. A (good): Can be easily peeled off. B (bad): The entire surface cannot be peeled off.
[0110] (Electrostatic properties) For samples rated A for release performance, the static voltage on the first surface of the release film was measured immediately after release. A surface potentiometer MP-520-1 (manufactured by Green Safety Co., Ltd.) was used as the static voltage measurement instrument, with the release film and the measurement terminals held at a fixed distance of 3 cm. The measured value was rounded to the nearest 1 V (the device's upper limit for measurement is 2000 V). The evaluation criteria for static electricity were as follows. A (good): |0~30|V B (pass): greater than |30|V and less than |50|V C(bad): greater than |50|V
[0111] (Residual glue) For samples with a release rating of A, the surface of the cured resin was observed using an optical microscope (100x magnification) after peeling to see if there was any transfer material from the release film. The evaluation criteria for residual adhesive were as follows. A (good): No transferred matter was observed on the surface of the cured product. B (bad): Transferred material was observed on the surface of the cured product.
[0112] (Laser Marking Visibility Evaluation) <Preparation of sealing body> The films of each example were used as release films, a semiconductor sealing epoxy resin (SumikonEME G770H type F ver. GR (manufactured by Sumitomo Bakelite Co., Ltd.)) was used as a curable resin, and a transfer molding device (G-LINE Manual System, Yamada Advanced Technology Co., Ltd.) was used as a sealing device. Sealed bodies for laser marking visibility evaluation were prepared according to the following procedures.
[0113] The mold temperature was set at 175°C, and a 70mm x 230mm copper lead frame and a 190mm wide release film roll were set up in a roll-to-roll configuration. The lead frame was placed in the lower mold, and the release film was vacuum-applied to the upper mold. After the molds were closed, curable resin was injected. After pressurization for 5 minutes, the mold was opened and the sealed package was removed. The film rated B for releasability had abnormal separation due to the cured product of the sealing resin and a portion of the release film not being released during mold opening, while the film rated A for releasability had no abnormal separation.
[0114] Laser Marking The color-changing pattern (printed characters) of the laser marking layer was formed using a 1064nm wavelength laser marker (MD-X1000, manufactured by Keyence Corporation). Laser marking conditions were: print count: 1, scan speed: 1000mm / s, frequency: 100kHz, laser power: 20%, print thickness: 0.3mm, line count: 5, and spot variable: -20. The printed characters were a 10-character alphabet (ABCDEFGHIJ), with a character height of 2.0mm, a width of 1.5mm, and character spacing of 0.5mm. The resulting laser markings (printed characters) were evaluated for legibility.
[0115] <Marking visibility> Fifty packages on which 10 alphabetical characters (ABCDEFGHIJ) were printed by laser marking were evaluated, and a reading test was performed on all packages, that is, 500 characters. The evaluation criteria for visibility are as follows. A (Good): All 500 characters can be read, with a reading rate of 100%. B (Pass): 1 or 2 characters cannot be read, and the reading rate is 99.8% or 99.6%. C (bad): Three or more characters cannot be read, and the reading rate is below 99.4%.
[0116] In addition, "readable" refers to a reading score of 80 to 99, and a score of less than 80 is considered unreadable. The reading score is evaluated using a high-speed, high-capacity flexible image processing system manufactured by Keyence Corporation. In addition, as long as the incident angle of the red LED is set to 20° to 70° relative to the horizontal plane of the package surface and the inspection camera is at right angles to the horizontal plane of the package, the device used for the evaluation is not limited. The following basic conditions reproduce the conditions used by representative laser recognition evaluation devices, such as KLA's ICOS component inspection devices CI-9X50 and CI-G10.
[0117] Measuring equipment High-capacity controller: XG-X2700 16x speed 21-megapixel monochrome camera: CA-H2100M 4 / 3-inch 50mm lens: CA-LHE50 (depth of focus ±2.5mm) Red lighting arch light (red lighting dome) Φ152: CA-DDR15 Application software: XG-X2000Series Ver.2.2
[0118] Measurement conditions Measurement area per data: 6.48 μm × 6.48 μm (42 μm 2 ) Distance between the sample and the lens: While monitoring the brightness of the non-marked area at a temporary distance of 170 mm, find the position showing maximum brightness and shorten it by 1.0 mm from that position. A red LED arch was set up with the incident angle relative to the package surface varying from 20° to 70°, and a camera was positioned perpendicular to the package surface. The camera had an ISO sensitivity of 3.0, a shutter speed of 20msec, an illumination intensity of 511, and a grayscale of 14. The lens had an aperture of 2.8.
[0119] Reading score Readability scores were calculated using OCR2 in the XG-X2000Series Ver.2.2 application software. Ten characters (A, B, C, D, E, F, G, H, I, and J) from a qualified product with no readability issues (character size: 2.0 mm vertically, 1.5 mm horizontally, with 0.5 mm character spacing) were pre-registered in a rectangular area that would fit the characters. The laser-marked characters on each package sample were then read. The characters on the registered good products are compared with the characters on the package surface to determine a reading score (a reading score of 99 is the best).
[0120] (Brightness of non-marked area) The same method as the laser marking visibility evaluation was used to prepare a sealed body, and the brightness of the sealed body was evaluated using the high-speed, high-capacity flexible image processing system manufactured by KEYENCE Corporation. 2 The same conditions as for the visibility evaluation were used. Brightness is expressed as a numerical value ranging from 0 to 255, with 0 corresponding to the dark side and 255 corresponding to the bright side. The measurement area was divided into 6.48 μm × 6.48 μm blocks, and the brightness was measured for each block. Therefore, brightness was calculated as the brightness distribution within the measurement area. The average brightness was calculated from the average brightness distribution within the measurement area. The average brightness of the laser-marked area was 160.
[0121] Materials used (Base material) ETFE film: The following ETFE (1) or ETFE (2) was used to prepare the ETFE film. The method for preparing the ETFE film is described in each example. ETFE (1): Fluon (registered trademark) ETFE C-88AXP (manufactured by AGC Corporation) ETFE (2): Fluon (registered trademark) LM-ETFE LM-720AP (manufactured by AGC Corporation)
[0122] PMP (polymethylpentene) film: Mitsui Chemicals Tocell Co., Ltd.: X-88BMT4, 50 μm thick, embossed on both sides (arithmetic mean height Sa of each surface is 2.5 μm and 1.4 μm) PET (Polyethylene terephthalate) film: Unitika Co., Ltd. S-38 (LS), a 38 μm thick biaxially oriented polyethylene terephthalate film. One surface of the film was treated with a sandmat for roughening. The arithmetic mean surface heights (Sa) were 1.6 μm and 0.1 μm, respectively.
[0123] SPS (syndiotactic polystyrene) film: XAREC (registered trademark) 142ZE (manufactured by Idemitsu Kosan Co., Ltd.) was fed into an extruder equipped with a T-die, drawn between mirror-finished metal rollers, and stretched simultaneously in the film's forward and perpendicular directions to produce a 50 μm thick film. The extruder and T-die temperatures were 270°C, the cooling roller temperature was 100°C, the stretching temperature was 115°C, the stretch ratio in both the forward and perpendicular directions was 3.3x, and the stretching speed was 500% / min. After the stretching step, the film was heat-treated at 215°C. Furthermore, sandblasting with a sand pad was performed to create irregularities on one surface of the film. The surface arithmetic mean heights (Sa) were 1.9 μm and 0.1 μm, respectively.
[0124] The surface with the higher arithmetic mean height Sa of each film was corona treated to adjust the wetting tension based on ISO 8296:1987 (JIS K6768:1999) to 40 mN / m or more. If the arithmetic mean height Sa of both surfaces was the same, one surface was corona treated.
[0125] (Antistatic coating liquid) 10 parts by mass of a polythiophene conductive polymer dispersion containing an acrylic resin (ARACOAT (registered trademark) AS601D (solid content 4% by mass, manufactured by Arakawa Chemical Industries, Ltd.)) and 1 part by mass of a multifunctional aziridine compound curing agent (ARACOAT (registered trademark) CL910 (solid content 10% by mass, manufactured by Arakawa Chemical Industries, Ltd.)) were mixed. The obtained mixture was diluted with a mixed solvent of isopropyl alcohol / toluene / water = 50 / 40 / 10 (mass ratio) to achieve the solid content concentration of each example, thereby obtaining an antistatic layer liquid. In addition, the surface resistivity of the antistatic layer itself after the antistatic layer described later was formed was 7×10 7 Ω / □.
[0126] (Mold release liquid) Release layer liquid (1): 100 parts by mass of Nissetsu (registered trademark) KP2562 (manufactured by Nippon Carbide Industries, Ltd., solid content 35% by mass, hydroxyl-containing (meth)acrylic polymer (hydroxyl value 70 mgKOH / g, crosslinking functional group equivalent 801 g / mol)), 6 parts by mass of Nissetsu (registered trademark) CK157 (manufactured by Nippon Carbide Industries, Ltd., solid content 100% by mass, trifunctional isocyanate compound (isocyanurate-type hexamethylene diisocyanate)), and 21 parts by mass of Nissetsu (registered trademark) CK-939 (manufactured by Nippon Carbide Industries, Ltd., solid content 0.5% by mass, acetylacetone solution of dioctyltin dilaurate) were mixed. The obtained mixture was diluted with ethyl acetate to obtain the solid content concentration of each example to obtain a release layer liquid.
[0127] Release layer liquid (2-1): 10 parts by mass of TAFTIC FH-S005 (trade name: acrylic particles, average particle size: 5 μm, manufactured by Toyobo Co., Ltd.) as resin particles were added to the release layer liquid (1) before dilution with ethyl acetate solvent, and the mixture was diluted with ethyl acetate to a solids concentration of 26% by mass to obtain a release layer liquid. The content of acrylic particles in the release layer formed from this release layer liquid was 16.9% by volume. Release layer liquid (2-2): A release layer liquid was obtained by the same procedure as for release layer liquid (2-1), except that the amount of TAFTIC FH-S005 was changed to 2 parts by mass. The acrylic particle content in the release layer formed from this release layer liquid was 3.9% by volume.
[0128] Release layer liquid (3-1): 10 parts by mass of SUNSPHEREL H-31 (manufactured by AGC Si-tech Co., Ltd., silicon oxide particles, average particle size 3 μm) were added to the release layer liquid (1) before dilution with ethyl acetate solvent, and the mixture was diluted with ethyl acetate to a solids concentration of 20% by mass to obtain a release layer liquid. The release layer formed from this release layer liquid had a silicon oxide particle content of 11.9% by volume. Release layer liquid (3-2): A release layer liquid was prepared by the same procedure as for release layer liquid (3-1), except that the amount of SUNSPHEREL H-31 (trade name, AGC Si-tech Co., Ltd., silicon oxide particles, average particle size 3 μm) was changed to 3.5 parts by mass. The release layer formed from this release layer liquid had a silicon oxide particle content of 4.5% by volume.
[0129] [Example 1] ETFE (1) was fed into an extruder, the die lip opening was adjusted so that the film thickness reached 50 μm, and the film was melt-extruded at 320°C by the extruder. Two original die rolls with concave and convex surfaces were used, and the film forming speed was adjusted and extracted to produce ETFE films with concave and convex structures on both surfaces. The arithmetic mean heights Sa of the two surfaces were 2.5 μm and 2.5 μm, respectively. One surface of the ETFE film was further subjected to corona treatment. An antistatic coating solution with a solids concentration of 4.0% by mass was applied to the corona-treated surface of the ETFE film using a gravure coater and dried to form an antistatic layer with a thickness of 0.25 μm. Coating was performed using a 100 mm x 250 mm wide, 150-meter, 40 μm deep roll as the gravure plate, using a direct gravure coating method at a coating speed of 4 m / min. Drying was performed in a roller-supported drying oven at 100°C for 1 minute with an air volume of 15 m / sec. A release layer liquid (1) having a solid content concentration of 13% by mass was applied to the antistatic layer using a gravure coater and dried to form a release layer having a thickness of 1.0 μm. Coating was performed using a direct gravure method, using a 150# cell with a width of Φ100 mm × 250 mm and a depth of 40 μm as a gravure. Drying was performed by passing the film through a roller-supported drying oven at a temperature of 100° C. for 1 minute at an air volume of 19 m / s. Subsequently, the film was cured at 40° C. for 120 hours to obtain a release film.
[0130] [Example 2] The same method as Example 1 is adopted, but one original mold roller is changed and the film forming speed is adjusted to produce an ETFE film having an arithmetic mean height Sa of 1.9 μm and 1.3 μm on the two surfaces, respectively. The surface on the side with a higher arithmetic mean height Sa is subjected to corona treatment, and an antistatic layer liquid with a solid content concentration of 3.2% by mass is further used to form an antistatic layer to obtain a release film.
[0131] [Example 3] The same method as in Example 2 was used, except that ETFE (2) was used as the resin, the film-forming speed was adjusted, and an ETFE film having a thickness of 60 μm and an arithmetic mean height Sa of 2.0 μm and 1.4 μm on both surfaces was manufactured. The surface on the side with the higher arithmetic mean height Sa of the film was subjected to corona treatment, and an antistatic layer liquid having a solid content concentration of 4.0% by mass was further used to form an antistatic layer. Subsequently, a release layer liquid (1) having a solid content concentration of 16% by mass was used to form a release layer to obtain a release film.
[0132] [Example 4] The same method as in Example 2 was adopted, but the film forming speed was adjusted to produce an ETFE film having an arithmetic mean height Sa of 1.7 μm and 1.7 μm on the two surfaces, respectively. An antistatic layer was formed on the surface subjected to corona treatment using an antistatic layer liquid having a solid content concentration of 2.4% by mass, and then a release layer liquid (1) having a solid content concentration of 29% by mass was used to form a release layer to obtain a release film.
[0133] [Example 5] The same method as in Example 1 is adopted, except that one original mold roller is not used. The film forming speed is adjusted to produce an ETFE film having an arithmetic mean height Sa of 1.6 μm and less than 0.05 μm on both surfaces, respectively. The surface on the side with a higher arithmetic mean height Sa is subjected to corona treatment, and an antistatic layer and a release layer are further formed to obtain a release film.
[0134] [Example 6] A release film was obtained in the same manner as in Example 3 except that an antistatic layer liquid having a solid content concentration of 6.9% by mass and a release layer liquid (1) having a solid content concentration of 10% by mass were used.
[0135] [Example 7] A release film was obtained in the same manner as in Example 6 except that the release layer liquid (1) having a solid content concentration of 2.6% by mass was used.
[0136] [Example 8] The same method as in Example 3 was adopted, but the film forming speed was adjusted to produce an ETFE film having a thickness of 70 μm and an arithmetic mean height Sa of 1.4 μm and 1.0 μm on both surfaces, respectively. The surface on the side having a higher arithmetic mean height Sa was subjected to corona treatment, and an antistatic layer liquid having a solid content concentration of 5.0% by mass was further used to form an antistatic layer. Subsequently, a release layer liquid (1) having a solid content concentration of 2.5% by mass was used to form a release layer to obtain a release film.
[0137] [Example 9] A release film was obtained in the same manner as in Example 8 except that the release layer liquid (1) having a solid content concentration of 5.6% by mass was used.
[0138] [Example 10] A release film was obtained in the same manner as in Example 8 except that the release layer liquid (1) having a solid content concentration of 7.2% by mass was used.
[0139] [Example 11] A release film was obtained in the same manner as in Example 1 except that a PMP film was used instead of the ETFE film.
[0140] [Example 12] A release film was obtained in the same manner as in Example 1 except that a PET film was used instead of the ETFE film and a release layer liquid (1) having a solid content concentration of 7.8% by mass was used.
[0141] [Example 13] A release film was obtained in the same manner as in Example 12 except that an SPS film was used instead of the ETFE film.
[0142] [Example 14] A release film was obtained in the same manner as in Example 8 except that an antistatic layer liquid having a solid content concentration of 4.2% by mass and a release layer liquid (1) having a solid content concentration of 1.3% by mass were used.
[0143] [Example 15] The same procedure as in Example 1 was followed, but the film forming speed was adjusted to produce an ETFE film having arithmetic mean heights Sa of 1.6 μm and 1.6 μm on both surfaces, respectively. A release layer liquid (1) having a solid content concentration of 31% by mass was used to obtain a release film.
[0144] [Example 16] A release film was obtained in the same manner as in Example 3 except that an antistatic layer liquid having a solid content concentration of 6.9% by mass and a release layer liquid (1) having a solid content concentration of 36% by mass were used.
[0145] [Example 17] A release film was obtained in the same manner as in Example 8 except that the release layer liquid (1) having a solid content concentration of 31% by mass was used.
[0146] [Example 18] The same procedure as in Example 5 was followed except that an antistatic layer liquid having a solid content concentration of 1.6% by mass was used to form an antistatic layer, and then a release layer liquid (1) having a solid content concentration of 20% by mass was used to form a release layer to obtain a release film.
[0147] [Example 19] A release film was obtained in the same manner as in Example 8 except that the antistatic layer and the release layer were not formed.
[0148] [Example 20] A release film was obtained in the same manner as in Example 1 except that the release layer was not formed.
[0149] [Example 21] A release film was obtained in the same manner as in Example 3 except that the release layer was not formed.
[0150] [Example 22] A release film was obtained in the same manner as in Example 8 except that the release layer was not formed.
[0151] [Example 23] The same procedure as in Example 5 was followed, except that the release layer liquid (2-1) was used instead of the release layer liquid (1), and the surface side with the lower arithmetic mean height Sa was subjected to corona treatment to further form an antistatic layer and a release layer to obtain a release film.
[0152] [Example 24] A release film was obtained in the same manner as in Example 1 except that the release layer liquid (2-1) was used instead of the release layer liquid (1).
[0153] [Example 25] A release film was obtained in the same manner as in Example 1 except that the release layer liquid (2-2) was used instead of the release layer liquid (1).
[0154] [Example 26] A release film was obtained in the same manner as in Example 1 except that the release layer liquid (3-1) was used instead of the release layer liquid (1).
[0155] [Example 27] A release film was obtained in the same manner as in Example 1 except that the release layer liquid (3-2) was used instead of the release layer liquid (1).
[0156] The release films of Examples 1 to 27, the sealed bodies prepared using these release films, and the sealed bodies after laser marking were subjected to the above-mentioned evaluations. The results are shown in Tables 1 to 3.
[0157] [Table 1]
[0158] [Table 2]
[0159] [Table 3]
[0160] As shown in the above results, the release films of Examples 1-13 and 23-27 comprise a release layer, an antistatic layer, and a substrate. The release layer has an average thickness exceeding 0.1 μm, and an existence fraction (Φ) of 0.12 or greater within the 10-35° range on the first surface, demonstrating excellent releasability and antistatic properties. Furthermore, sealed bodies manufactured using the release films of Examples 1-13 and 23-27 not only suppress abnormal brightness caused by resin flow marks or damage on the surface of the semiconductor package, but also exhibit surfaces that are highly legible for laser marking.
[0161] As a feature of recognizability, if the average brightness difference between the laser marking portion and the non-marking portion is large, contrast will be generated and the recognizability will be optimized. From the above evaluation results, it can be seen that from the perspective of increasing the contrast, the average brightness of the non-marking portion is preferably below 100, and more preferably below 95. On the other hand, it is known that the phenomenon of increased brightness of a part of the surface caused by resin flow marks (flow marks) on the surface of the package at the non-marking portion or damage to the surface of the package will cause the reading rate to decrease, so the average brightness of the non-marking portion is preferably above 55, and more preferably above 60.
[0162] The present invention has been described in detail or with reference to specific embodiments, but it will be apparent to those skilled in the art that various changes and modifications may be made without departing from the spirit and scope of the present invention. This application is based on Japanese patent application (Japanese Patent Application No. 2023-015583) filed on February 3, 2023, the contents of which are incorporated herein by reference. Possibility of industrial application
[0163] The mold release film disclosed herein can form a semiconductor package surface having excellent antistatic properties, mold release properties from the semiconductor package, and excellent laser marking visibility. Using the mold release film disclosed herein, a semiconductor package having a surface having excellent laser marking visibility can be manufactured. Explanation of symbols
[0164] 1A package sealing body, 10 substrate, 12 semiconductor chip (semiconductor element), 19 cured product, 20 fixed upper mold, 22 cavity bottom member, 24 movable lower mold, 26 cavity, 30 release film, 32 surface unevenness of release film, 40 curable resin, 50 upper mold, 52 lower mold, 54 cavity, 56 cavity surface, 58 substrate setting portion, 60 resin introduction portion, 62 resin placement portion, 64 plunger
Claims
1. A release film comprising a release layer, an antistatic layer and a substrate in this order, wherein: The average thickness of the release layer is greater than 0.1 μm, When the surface irregularities on the release layer side of the release film are measured using a laser microscope and the surface angle distribution of the angle (θ) formed by the normal vector of the irregularities and the normal to the main surface of the release film is calculated, the existence fraction (Φ) in the range of 10 to 35° is greater than 0.
12.
2. The release film according to claim 1, wherein An arithmetic mean height Sa of at least one surface of the substrate is greater than or equal to 0.9 μm.
3. The release film according to claim 2, wherein An arithmetic mean height Sa of the surface of the substrate on the antistatic layer side is 1.2 μm or more.
4. The release film according to any one of claims 1 to 3, wherein The content of particles in the release layer is 25% by volume or less.
5. The release film according to claim 1 or 2, wherein The substrate includes a fluororesin. The release film according to claim 5 , wherein The fluororesin includes an ethylene-tetrafluoroethylene copolymer.
7. The release film according to claim 1 or 2, wherein The surface resistivity of the release layer side surface is 1×10 7 ~1×10 11 Ω / □. 8 . The release film according to claim 1 , which is arranged between a curable resin and a surface of a mold in the production of a semiconductor package.
9. The release film according to claim 8, wherein The surface of the release film on the release layer side is in contact with the curable resin.
10. A method for manufacturing a semiconductor package comprising a semiconductor element and a resin sealing portion formed of a curable resin for sealing the semiconductor element, wherein: The substrate having the semiconductor element is arranged in the cavity of the mold, On the cavity surface of the mold where the substrate is not disposed, the release film according to claim 1 or 2, which comprises a release layer, an antistatic layer, and a base material, is disposed so that the surface on the release layer side faces the space in the cavity. The cavity is filled with the curable resin, and the curable resin is cured in a state where the curable resin is in contact with the release film, thereby forming a resin sealing portion that seals the semiconductor element.
Citation Information
Patent Citations
Sealing sheet for semiconductor elements, semiconductor device, and method for manufacturing semiconductor device
JP2014179593A
Game machine
JP2023015583A